Trace elemental analysis and antimicrobial activities of Elephantopus scaber L. - Santhosh Kumar, S; Subramanian, A; Uma, C; Rengaiyan, R; Sambandan, K; Sekar, K G; Sudarshan, M; Chakraborty, A (Journal of Phytology, 2012)
Screening of various Indian medicinal plants has various degrees of antimicrobial activities against pathogenic and opportunistic microorganisms. Since the number of effective exogenous antibiotics is decreasing, concerted efforts are to be made to identify antimicrobial materials from natural products and traditional medicines. In the present study, we are reporting the antimicrobial activity of the traditionally used Ayurvedic medicinal plant Elephantopus scaber and its elemental composition analysis. The antimicrobial activities are found to be higher in leaf extracts of Elephantopus scaber whereas no inhibition was found for root extracts. The elements such as Si, Ca, Cl, Mg, S, K and P are more abundant in the leaf than the root whereas heavy metals are higher in roots than in leaves. In the root, presence of Al, Fe, Ti, Sr, and V is more when compared to leaves whereas Zn, Cu, As, Rb and Sr are less available and are equally present in roots as well as leaf. The elements Cr, Co, Ni, Se, Br and Pb are not found in both leaves and roots.